2021
DOI: 10.1002/adfm.202100233
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Atom Co‐Decorated MoS2 Nanosheets Assembled on Metal Nitride Nanorod Arrays as an Efficient Bifunctional Electrocatalyst for pH‐Universal Water Splitting

Abstract: The commercialization of electrochemical water splitting technology requires electrocatalysts that are cost‐effective, highly efficient, and stable. Herein, an advanced bifunctional electrocatalyst based on single‐atom Co‐decorated MoS2 nanosheets grown on 3D titanium nitride (TiN) nanorod arrays (CoSAs‐MoS2/TiN NRs) has been developed for overall water splitting in pH‐universal electrolytes. When applied as a self‐standing cathodic electrode, the CoSAs‐MoS2/TiN NRs requires overpotentials of 187.5, 131.9, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(49 citation statements)
references
References 68 publications
0
44
0
Order By: Relevance
“…This demanded development of suitable OER/HER catalysts capable of reducing activation energy involved in the water-splitting process. In this regard, platinum (Pt) and Ru/Ir exhibited outstanding electrocatalytic activity in HER and OER, respectively. However, high cost, low availability, and poor stability mark significant limitations for their commercial and technological applications.…”
Section: Introductionmentioning
confidence: 99%
“…This demanded development of suitable OER/HER catalysts capable of reducing activation energy involved in the water-splitting process. In this regard, platinum (Pt) and Ru/Ir exhibited outstanding electrocatalytic activity in HER and OER, respectively. However, high cost, low availability, and poor stability mark significant limitations for their commercial and technological applications.…”
Section: Introductionmentioning
confidence: 99%
“…29–31 The two other peaks at 779.48 eV and 801.78 eV may be attributed to the strong interaction between the Co–Mo bond and the cobalt nanoparticles and MoS 2 phase, respectively. 32–34…”
Section: Resultsmentioning
confidence: 99%
“…It is found that there is a relatively large charge transfer between NiCo 2 O 4 and NiCo­(OH) 2 . The charge is mainly transferred from NiCo­(OH) 2 to NiCo 2 O 4 , which leads to the strong interlayer interaction. According to the Tafel slope value, the catalytic HER process using the NiCo 2 O 4 @NiCo­(OH) 2 /PNCF electrode follows the Volmer–Heyrovsky mechanism, whereas the Heyrovsky step is the rate-determining step: …”
Section: Resultsmentioning
confidence: 99%
“…According to the Tafel slope value, the catalytic HER process using the NiCo 2 O 4 @NiCo­(OH) 2 /PNCF electrode follows the Volmer–Heyrovsky mechanism, whereas the Heyrovsky step is the rate-determining step:…”
Section: Resultsmentioning
confidence: 99%